Intregasi Model Pembelajaran Pesantren Di Sekolah Formal: Studi Kasus Di SMP Islam As-Syafiah Mojosari Kec. Loceret Nganjuk - Nafi, Dedik Muksinun; Wasito (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
This research focuses on applying the concept of integration of pesantren learning models in schools. The location of this study in As-Syaf’iah Islamic School, Mojosari Kec. Loceret, Nganjuk. The selection of this concentration, as evidence from previous studies that are modelled. The purpose of this study is to describe the pesantren-based learning model implemented in the As-Syafi'ah Mojosari Islamic Middle School. To analyze aspects that contribute to the implementation of the pesantren based learning model in As-Syafi'ah Mojosari Islamic Middle School. This research uses a descriptive qualitative approach. This study uses interviews, observation and documentation as a way to explore data. The data that has been collected will be analyzed and described in accordance with research concentrations. The results of this study can be conveyed that the pesantren-based Learning model implemented in As-Syafi'ah Mojosari Islamic Middle School runs without changing the typical pesantren. All activities are carried out by all students who are also students in As-Syafi'ah Islamic Middle School. The smooth running of these activities is supported by the mandatory boarding program, so that supervision of all santri is very easy, moreover supported by the location of school buildings and dormitories in one area located in the middle of Ngepeh village. In addition to the mandatory boarding program, there are also tahfidz and entrepreneurship programs. The tahfidz program in question is obligatory to memorize the Qur'an Juz 30 and it is recommended to memorize all the Qur'an.